Comparison of Hajj Financial Management in Malaysia and Indonesia - Ngah, Abdul Ghani Bin (Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The historical experience of organizing Hajj in Malaysia and Indonesia is long enough that the Malaysian Hajj Savings Institution (TH) and the Hajj Financial Management Agency (BPKH) were formed to manage the pilgrimage for the people of Malaysia and Indonesia. However, in practice, there are still many debates in terms of the use of contracts, Hajj management, facilities and human resources that have not been improved. This study aims to compare contract construction related to hajj performance which has an impact on haj financial management with a business and investment approach. This study uses a qualitative method using a document coding model. The data was obtained using a comparative normative approach, namely by exploring information about the contract, the impact of the contract on the financial management of the hajj in Malaysia and Indonesia. The results of this study can be concluded that the two countries use the Wakalah contract as the construction of the Hajj contract where the contract fulfills the pillars and conditions, but with a note that the other contract schemes still use the